2003
DOI: 10.1194/jlr.m200405-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat modulation of apoA-II metabolism and prevention of senile amyloidosis in the senescence- accelerated mouse

Abstract: Senescence-accelerated mouse-prone (SAMP1; SAMP1@Umz) is an animal model of senile amyloidosis with apolipoprotein A-II (apoA-II) amyloid fibril (AApoAII) deposits. This study was undertaken to investigate the effects of dietary fats on AApoAII deposits in SAMP1 mice when purified diets containing 4% fat as butter, safflower oil, or fish oil were fed to male mice for 26 weeks. The serum HDL cholesterol was significantly lower ( P Ͻ 0.01) in mice on the diet containing fish oil (7.4 ؎ 3.0 mg/dl) than in mice on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
(35 reference statements)
0
10
1
1
Order By: Relevance
“…Previous studies have shown that a diet heavy in butter, saturated fatty acids, or fish oil with n -3 PUFAs, advances the severity of age-related senile amyloidosis, whereas soybeans enriched with n -6 PUFAs alleviate the severity of the age-related disease ( 19 ). These findings are contrary to the popular hypothesis that n -3 PUFAs are beneficial to health.…”
contrasting
confidence: 56%
“…Previous studies have shown that a diet heavy in butter, saturated fatty acids, or fish oil with n -3 PUFAs, advances the severity of age-related senile amyloidosis, whereas soybeans enriched with n -6 PUFAs alleviate the severity of the age-related disease ( 19 ). These findings are contrary to the popular hypothesis that n -3 PUFAs are beneficial to health.…”
contrasting
confidence: 56%
“…In our previous study, we reported that SAMP1 mice that were fed a fish oil diet had significantly lower apoA-II concentrations but more AApoAII deposits than those on a butter and safflower oil diet. 38 These results suggested altered metabolism or clearance of amyloid protein might be another factor controlling susceptibility towards amyloidosis. 39 ApoA-II is synthesized mainly in the liver in mice and secreted to the blood very quickly.…”
Section: Discussionmentioning
confidence: 88%
“…In this experiment, HDL appeared monotonic ( Fig. 2A ), and we marked size classes of HDL 1 , HDL 2 , and HDL 3 based on the distributions of apoA-I and apoA-II in WT mice and our previously reported results ( 14,29 ).…”
Section: Isolation Of Amyloid Fi Brilsmentioning
confidence: 99%
“…Electrophoresis was carried out at 25 mA for 2 h ( 14,29 ). The distribution of apoA-I, apoA-II, apoE, apoA-IV, and apoC-II protein among the HDL species was determined by Western blot analysis of 0.5, 2, 1, 1, and 2 l plasma, respectively, separated by nondenaturing PAGE.…”
Section: Lipoprotein Quantity Hdl Particle Size and Distribution Ofmentioning
confidence: 99%